Respuesta :

Answer:

y = -4x+7 is the equation simplified and answer choice A is the right answer.

Step-by-step explanation:

Your equation: y - 6 = -4(x+1)

Your Objective: You need to simplify the original equation and find another equation that is equivalent to the original equation.


Let's focus on the -4(x+1) side first.

This needs to have the distributive property applied.

Take -4 and multiply it by x and 1.

You should have -4x+1

Your equation now:

y - 6 = -4x+1

We want y to be by itself.

So add 6 to both sides.

y = -4x+1+6


Use PEMDAS

y = -4x+7


The first answer choice "A" is correct.

Otras preguntas